Association of the X-chromosomal genes TIMP1 and IL9R with rheumatoid arthritis - Burkhardt, Jana; Petit-Teixeira, Elisabeth; Teixeira, Vitor Hugo; Kirsten, Holger; Garnier, Sophie; Ruehle, Sandra; Oeser, Christian; Wolfram, Grit; Scholz, Markus; Migliorini, Paola; Balsa, Alejandro; Westhovens, Renè; et al. (The Journal of rheumatology, 2009)
OBJECTIVE\backslashr\backslashnRheumatoid arthritis (RA) is an inflammatory joint disease with features of an autoimmune disease with female predominance. Candidate genes located on the X-chromosome were selected for a family trio-based association study.\backslashr\backslashnMETHODS\backslashr\backslashnA total of 1452 individuals belonging to 3 different sample sets were genotyped for 16 single-nucleotide polymorphisms (SNP) in 7 genes. The first 2 sets consisted of 100 family trios, each of French Caucasian origin, and the third of 284 additional family trios of European Caucasian origin. Subgroups were analyzed according to sex of patient and presence of anti-cyclic citrullinated peptide (anti-CCP) autoantibodies.\backslashr\backslashnRESULTS\backslashr\backslashnFour SNP were associated with RA in the first sample set and were genotyped in the second set. In combined analysis of sets 1 and 2, evidence remained for association of 3 SNP in the genes UBA1, TIMP1, and IL9R. These were again genotyped in the third sample set. Two SNP were associated with RA in the joint analysis of all samples: rs6520278 (TIMP1) was associated with RA in general (p = 0.035) and rs3093457 (IL9R) with anti-CCP-positive RA patients (p = 0.037) and male RA patients (p = 0.010). A comparison of the results with data from whole-genome association studies further supports an association of RA with TIMPL The sex-specific association of rs3093457 (IL9R) was supported by the observation that men homozygous for rs3093457-CC are at a significantly higher risk to develop RA than women (risk ratio male/female = 2.98; p = 0.048).\backslashr\backslashnCONCLUSION\backslashr\backslashnWe provide evidence for an association of at least 2 X-chromosomal genes with RA: TIMP1 (rs6520278) and IL9R (rs3093457).